ASSOCIAÇÃO ENTRE FATOS GEOMÓRFICOS E OS DOBRAMENTOS DE FUNDO NA EVOLUÇÃO DE UMA REDE DE DRENAGEM NA MARGEM ATLÂNTICA DO PLANALTO BRASILEIRO: O CASO DA BACIA HIDRÓGRÁFICA DO RIO BENEVENTE – ES - Vervloet, Roberto José; Ross, Jurandyr Luciano Sanches (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2013)
The issues addressed in this article refer to the concluding part entitled research Morphologic and Structural Dynamics Constraints in the river basin of Rio hydroghaphy Benevente – Espirito Santo which aimed to investigate the lithostructural, tectonic, morphologic factors as constrain the in evolution of the drainage network of Benevente, river basin located in the south of Espírito Santo, state, Brazil. In this article it’s present the fold of background, studied by Ruellan (1952), set out the basic levels in local and regional erosion process, while also affects the evolution of the drainage network, as responsible for the dynamics of sub-compartments relief associated to lithostructural interface tectonic-relief-fluvial channels evolution. This article does homage to the pioneering work of Ruellan regarding the geomorphologic studies about Brazilian territory.